Stressful life events and depressive symptoms among adolescents in Malaysia - Wong, Yi Shan (2019)
Little is known about the etiology of depression and its mechanism underlying the development of depressive symptoms in adolescents, particularly within the Malaysian context. As proposed by Beck’s cognitive theory of depression, cognitive vulnerabilities serve as critical components to the rise of depressive symptoms in response to stressors. Given that cognitive vulnerability-stress model consists of effective elements for targeted depression prevention and intervention programs, the present study aimed to provide a fundamental understanding on the mediational role of cognitive vulnerability factor (i.e., maladaptive cognitive schema) in the structural relationships between stressful life events (i.e., negative life events and daily hassles) and depressive symptoms among the adolescents and examine the potential moderation effect of gender on the overall model. A cross-sectional correlational study was conducted to recruit participants across four selected states (i.e., Kedah, Kelantan, Melaka, and Selangor) in Malaysia. The present study involved 1,032 adolescents (38.8% of male and 61.2% of female) with the mean age of 14.97 from 25 government secondary schools, identified using probability proportional to size cluster sampling technique. Data were collected through a selfadministered questionnaire, which comprised of the Life Events Checklist-Malay (Baharudin et al., 2016), Adolescent Minor Stress Inventory (Ames et al., 2005), Depression Anxiety Stress Scales Depression subscale (Lovibond & Lovibond, 1995), and Automatic Thought Questionnaire (Hollon & Kendall, 1980). The hypothesized model was tested using structural equation modeling analyses. Findings supported the direct impact of daily hassles on depressive symptoms but found no evidence for negative life events. As for the mediation test, bootstrapping results revealed that maladaptive cognitive schema significantly mediates the relationship between stressful life events (i.e., negative life events and daily hassles) and depressive symptoms. Results reported a full mediation effect of maladaptive cognitive schema between negative life events and depressive symptoms, and a partial mediation effect between daily hassles and depressive symptoms. Moderation analyses showed that the structural relationships between study variables differed across gender. Overall, the present study demonstrated the direct relationships between stressful life events and depressive symptoms and provides valuable insights on the mediating role of maladaptive cognitive schema in the stress-depression association. Findings advances the understanding of mechanism underlying development of depressive symptoms among adolescents in Malaysia.